(untitled) (Revista de Artes Marciales Asiáticas, 2012)
Miyagi Chojun (1888-1953) was the founder of Goju-ryu; a karate-do style that purportedly had ties to a Chinese boxing school established on Okinawa in 1828 and was based on the teachings of his primary instructor Higaonna Kanryo (1850-1915). Yet, the continuity of modern Goju-ryu with respect to its katas (forms) and these historical sources has never been established. Therefore, we employed a statistical technique to examine the relationship between the classical katas of modern Goju-ryu. It was reasoned that there would be continuity across all katas of modern Goju-ryu if they indeed came from a similar source. The results were insightful and suggest the possible origins of Goju-ryu katas.